Narrativas sobre la influencia de los estereotipos y creencias respecto a la sexualidad y su afectación en la motivación hacia el encuentro sexual en cuatro adultas mayores del club de la tercera edad Canitas y Sueños de la Ciudad de Bogotá (2019)
The present study aims to describe the experiences of sexuality and identify the sociocultural factors that are involved in the motivation towards the sexual encounter of adults over 60 to 80 years of age who belong to the Club of Older Adults of the City of Bogotá. For this, the descriptive, non-experimental method with qualitative scope and narrative type was used. The subjects under study were four adults over 60 to 80 years of age. The study found that motivation, considered a psychological factor, is low in the decision to maintain an active sex life, due to the influence of stereotypes and beliefs of a cultural, religious and social nature.